Environmental, resident and bystander exposure from spraying applications with unmanned aerial vehicles equipped with flat-fan nozzles or rotary atomizers - Pierre-Henri Dubuis; Céline Villars-Corbex; M. Clare Butler Ellis; H. Christoph Geiser; Jeremy J. Harwood; Marco C. Knobloch; Andrew G. Lane; Aurélie Melgar; Joel D. Stohler; Clive R. Tuck; Helen C. Wheeler; Jürg A. Zarn; et al. (Crop Protection, 2026)

Investigating reservoir-scale heterogeneity in Li-enriched oil field brines of the Devonian Leduc and Nisku formations, Alberta Basin, Canada - M.R. Blake; K.L. Butler; L.A. Munk; D.F. Boutt; N. Morris; J. Kennedy; P. Saha; J. Serotta; H. Tompkins; G. Williams; A. Vengosh; J. Evaristo; et al. (Applied Geochemistry, 2026)

Genomic connectivity and future climate suitability of the Caribbean king crab (Maguimithrax spinosissimus) highlight its potential for coral reef restoration - Pedro A. Peres; Natalie A. Whitaker-Allen; Mark J. Butler; Heather D. Bracken-Grissom (Conservation Genetics, 2026)

Investigating the origins of quarry populations of the Caribbean King Crab (Maguimithrax spinosissimus) to inform coral reef recovery efforts in the Florida Keys, Florida (USA) - Natalie A. Whitaker-Allen; Pedro A. Peres; Mark J. Butler; Heather D. Bracken-Grissom (Coral Reefs, 2026)

‘Building the (Im)perfect Beast’: Strategies for Identifying Appropriate Spatial Stock Assessment Model Complexity From an International, Blinded High‐Resolution Simulation Experiment - Aaron M. Berger; Daniel R. Goethel; Simon D. Hoyle; Patrick Lynch; Caren Barceló; Alistar Dunn; Brian J. Langseth; Carolina Minte‐Vera; Jemery Day; Haikun Xu; Francisco Izquierdo; Dan Fu; et al. (Fish and Fisheries, 2026)
Despite their potential to inform sustainable regional harvest and climate‐resilient fisheries management, spatial stock assessment models remain underused for management advice. To identify barriers that inhibit broader use of these methods, we conducted a blinded international simulation experiment mimicking real‐world stock assessment development when confronting spatial complexity. Seven analyst teams built spatially aggregated and spatially explicit assessment models using data simulated from high‐resolution operating models based on Indian Ocean yellowfin tuna and Ross Sea Antarctic toothfish dynamics. Each team documented how assessment software platform, data analyses, model building approach, and diagnostics influenced model complexity and realism. A consensus emerged on key assessment building approaches: (1) conduct high‐resolution data analyses to identify appropriate spatial structure; (2) start with simplified models and incrementally add complexity; (3) iteratively evaluate diagnostics to determine necessary spatial complexity; and (4) maintain models with different spatial structures to aid interpretation. The experiment also revealed several valuable insights for parameterising assessments, including consideration of data pre‐processing with spatiotemporal models to better inform data‐sparse regions; regression trees to identify fleet and spatial structure; trade‐offs in complexity between productivity and movement dynamics to achieve tractable and stable model structures; and ensemble modelling approaches to address structural uncertainty. Our findings demonstrate that international collaborations and simulation experiments are crucial for addressing challenges in implementing spatial stock assessments and for evaluating whether their added complexity is justified given management objectives. Broader collaborations are encouraged to foster innovation in fisheries management and to help recognise the practical trade‐offs between model parsimony and complexity.

A habitability lens to boost effective local climate adaptation - A.K. Magnan; V.K.E. Duvat; J. Bell; S.D. Donner; J.D. Ford; P.D. Nunn; C. Perry; T. Spencer; C.C.C. Wabnitz; I. White; J. Butler; A. McCarthy; et al. (Environmental Science & Policy, 2026)

Effects of environmental conditions on mate fidelity in a socially monogamous seabird - Sue Lewis; Adam Butler; Sarah Wanless; Mark A. Newell; Michael P. Harris; Sarah J. Burthe; Carrie M. Gunn; Richard J. Howells; Francis Daunt (Animal Behaviour, 2025)

First dinosaur remains from Serbia: Sauropod and theropod material from the uppermost Cretaceous (Maastrichtian) of Osmakovo - Zoran Marković; Miloš Milivojević; Richard J. Butler; Paul M. Barrett; Simon Wills; Andrew A. van de Weerd; Wilma Wessels; Predrag Radović (Cretaceous Research, 2025)

Repeated barrier drown-out is required to facilitate long-distance migration of a potamodromous fish - Jason D. Thiem; Benjamin G. Fanson; David Ryan; Gavin L. Butler; David A. Crook; Doug J. Harding; Anthony Townsend; Ian J. Wooden; Ivor Stuart (Aquatic Sciences, 2025)
Migratory fish species are highly vulnerable to stream fragmentation. Potamodromous golden perch ( Macquaria ambigua ) inhabit the barrier-laden Murray–Darling Basin (MDB), Australia’s largest river system, and its lifecycle includes a requirement for uninterrupted stretches of flowing water habitat. Owing to these barriers, large-scale connectivity in many regions is limited to periods of high flow events that facilitate barrier drown-out. We undertook a 3-year (2021–2024) study using telemetry to quantify the movements of 150 adult golden perch from the Barwon–Darling River over a period that encompassed numerous high flow events and flooding. Approximately 75% of tagged golden perch undertook movements > 50 km, with > 90% of movements in an upstream direction, extending up to 1500 km and associated with increased river discharge. Tributary entries were detected on multiple occasions, with an apparent preference for specific tributaries. Ten fish migrated > 1000 km upstream across multiple flow events. The results of this study (1) highlight the importance of the Barwon–Darling River and tributaries as a key migration conduit for adult golden perch, (2) demonstrate that multiple flow events are required to achieve large-scale dispersal and (3) provide quantitative flow-movement relationships that can be used to support inter-regional management actions. These management actions might include barrier removal, the construction of fishways and protection of tributary–mainstem flow events.

Performance of summary measures of core body temperature in heat-related health outcome regression models - M. Dally; A. Dye-Robinson; Y. Li; D. Jaramillo; K. Villarreal-Hernandez; L. Krisher; J. Butler-Dawson; J. Schaeffer; J. L. Adgate; K. A. James; L. S. Newman (International Journal of Biometeorology, 2025)

How Do Synchrony in Survival and Productivity Influence Abundance Synchrony in European Landbirds? - Catriona A. Morrison; Jennifer A. Gill; Claire Buchan; Robert A. Robinson; Juan Arizaga; Oriol Baltà; Emanuel Baltag; Jaroslav Cepák; Pierre‐Yves Henry; Ian Henshaw; Zsolt Karcza; Petteri Lehikoinen; et al. (Ecology Letters, 2025)
Synchronous fluctuations in species' abundance are influenced by synchrony in underlying rates of productivity and survival. However, it remains unclear how rate synchrony varies in space and time, contributes to abundance synchrony, and differs among species. Using long‐term annual count (number of adults captured), adult survival and productivity (number of juveniles captured per adult) data for breeding land‐birds at ringing sites across Europe, we show that synchrony is strongest and largest scale in productivity and weakest and smallest scale in counts. However, counts fluctuate more synchronously with survival than they do with productivity. These patterns hold for species which do not migrate or only migrate within Europe (European‐residents) and those migrating to sub‐Saharan Africa (subSaharan‐migrants), but the periodicity of productivity and survival synchrony is longer in European‐residents than in subSaharan‐migrants. This suggests that survival and productivity synchrony may interact to weaken abundance fluctuations but are influenced by environmental drivers operating over differing timescales in European‐resident and subSaharan‐migrant species.

All the light we cannot see: Climate manipulations leave short and long‐term imprints in spectral reflectance of trees - Artur Stefanski; Ethan E. Butler; Laura J. Williams; Raimundo Bermudez; J. Antonio Guzmán Q.; Andrew Larson; Philip A. Townsend; Rebecca Montgomery; Jeannine Cavender‐Bares; Peter B. Reich (Ecology, 2025)
Anthropogenic climate change, particularly changes in temperature and precipitation, affects plants in multiple ways. Because plants respond dynamically to stress and acclimate to changes in growing conditions, diagnosing quantitative plant‐environment relationships is a major challenge. One approach to this problem is to quantify leaf responses using spectral reflectance, which provides rapid, inexpensive, and nondestructive measurements that capture a wealth of information about genotype as well as phenotypic responses to the environment. However, it is unclear how warming and drought affect spectra. To address this gap, we used an open‐air field experiment that manipulates temperature and rainfall in 36 plots at two sites in the boreal‐temperate ecotone of northern Minnesota, USA. We collected leaf spectral reflectance (400–2400 nm) at the peak of the growing season for three consecutive years on juveniles (two to six years old) of five tree species planted within the experiment. We hypothesized that these mid‐season measurements of spectral reflectance capture a snapshot of the leaf phenotype encompassing a suite of physiological, structural, and biochemical responses to both long‐ and short‐time scale environmental conditions. We show that the imprint of environmental conditions experienced by plants hours to weeks before spectral measurements is linked to regions in the spectrum associated with stress, namely the water absorption regions of the near‐infrared and short‐wave infrared. In contrast, the environmental conditions plants experience during leaf development leave lasting imprints on the spectral profiles of leaves, attributable to leaf structure and chemistry (e.g., pigment content and associated ratios). Our analyses show that after accounting for baseline species spectral differences, spectral responses to the environment do not differ among the species. This suggests that building a general framework for understanding forest responses to climate change through spectral metrics may be possible, likely having broader implications if the common responses among species detected here represent a widespread phenomenon. Consequently, these results demonstrate that examining the entire spectrum of leaf reflectance for environmental imprints in contrast to single features (e.g., indices and traits) improves inferences about plant‐environment relationships, which is particularly important in times of unprecedented climate change.

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

Designing development programmes for climate change and uncertainty in Pacific Melanesia – the role for knowledge brokers - James R. A. Butler; Seona Meharg; Nicky Grigg; Emily J. Barbour; Hannah Barrowman; Danie Nilsson; Samantha Stone-Jovicich (Climate and Development, 2025)

Tree diversity shapes the spectral signature of light transmittance in developing forests - Laura J. Williams; Kyle R. Kovach; J. Antonio Guzmán Q.; Artur Stefanski; Raimundo Bermudez; Ethan E. Butler; Domitille Coq‐‐Etchegaray; Catherine Glenn‐Stone; Peter Hajek; Johanna Klama; Belinda E. Medlyn; Christian Messier; et al. (Ecology, 2025)
Greater tree diversity often increases forest productivity by increasing the fraction of light captured and the effectiveness of light use at the community scale. However, light may shape forest function not only as a source of energy or a cause of stress but also as a context cue: Plant photoreceptors can detect specific wavelengths of light, and plants use this information to assess their neighborhoods and adjust their patterns of growth and allocation. These cues have been well documented in laboratory studies, but little studied in diverse forests. Here, we examined how the spectral profile of light (350–2200 nm) transmitted through canopies differs among tree communities within three diversity experiments on two continents (200 plots each planted with one to 12 tree species, amounting to roughly 10,000 trees in total), laying the groundwork for expectations about how diversity in forests may shape light quality with consequences for forest function. We hypothesized—and found—that the species composition and diversity of tree canopies influenced transmittance in predictable ways. Canopy transmittance—in total and in spectral regions with known biological importance—principally declined with increasing leaf area per ground area (LAI) and, in turn, LAI was influenced by the species composition and diversity of communities. For a given LAI, broadleaved angiosperm canopies tended to transmit less light with lower red‐to‐far‐red ratios than canopies of needle‐leaved gymnosperms or angiosperm‐gymnosperm mixtures. Variation among communities in the transmittance of individual leaves had a minor effect on canopy transmittance in the visible portion of the spectrum but contributed beyond this range along with differences in foliage arrangement. Transmittance through mixed species canopies often deviated from expectations based on monocultures, and this was only partly explained by diversity effects on LAI, suggesting that diversity effects on transmittance also arose through shifts in the arrangement and optical properties of foliage. We posit that differences in the spectral profile of light transmitted through diverse canopies serve as a pathway by which tree diversity affects some forest ecosystem functions.

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Evaluating the sensitivity of a chronic plant bioassay relative to an independently derived predicted no-effect thresholds to support risk assessment of very hydrophobic organic chemicals - Aaron D. Redman; Miriam Leon Paumen; Daniel J. Letinski; Barbara A. Kelley; Cary Sutherland; Bryan M. Hedgpeth; Josh D. Butler; Roger Prince; Gail E. Bragin; Abraham J. Smith (Archives of Environmental Contamination and Toxicology, 2025)

Measuring the association between the opening of a new multi-national restaurant with young people's eating behaviours - Helen J. Moore; Claire L. O'Malley; Scott Lloyd; Fatemeh Eskandari; Kelly Rose; Mark Butler; Tim G. Townshend; Heather Brown; Daniel Clarkson; Amelia A. Lake (Appetite, 2024)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Use of multiple climate change scenarios to predict future distributions of alligator gar (Atractosteus spatula) in the United States - Jory Bartnicki; Richard A. Snow; Andrew T. Taylor; Christopher J. Butler (Environmental Biology of Fishes, 2024)

Thermal exposure risk in different life stages of Chinook salmon in the Nechako River system, British Columbia - Muhammed A. Oyinlola; Mostafa Khorsandi; Noa B. Mayer; Natalie Butler; Jacey C. Van Wert; Erika J. Eliason; Richard Arsenault; Colin J. Brauner; Scott G. Hinch; Andre St-Hilaire (Climatic Change, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A Double-blind, Randomized, Placebo-controlled Crossover Study Evaluating Reducose® Mulberry Leaf Extract at 3 Levels Shows Significant Effects on Postprandial Blood Glucose and Insulin After Eating a Complex Meal - B. Davis; P. Thondre; J. Tammam; I. Butler; M. Lane; A. Gallagher (Journal of the Academy of Nutrition and Dietetics, 2024)

Intercomparison of global foliar trait maps reveals fundamental differences and limitations of upscaling approaches - Benjamin Dechant; Jens Kattge; Ryan Pavlick; Fabian D. Schneider; Francesco M. Sabatini; Álvaro Moreno-Martínez; Ethan E. Butler; Peter M. van Bodegom; Helena Vallicrosa; Teja Kattenborn; Coline C.F. Boonman; Nima Madani; et al. (Remote Sensing of Environment, 2024)

Contribution of invasive carp (Cyprinus carpio) to fish biomass in rivers of the Murray–Darling Basin, Australia - Hayden T. Schilling; Gavin L. Butler; Katherine J. M. Cheshire; Dean M. Gilligan; Jerom R. Stocks; Jason D. Thiem; David A. Crook (Biological Invasions, 2024)
Following the introduction of the ‘Boolarra’ strain to Australia in the mid 1960’s, Common carp ( Cyprinus carpio ) rapidly spread in waterways across the Murray–Darling Basin (MDB) in southern-eastern Australia. A previous study of the population expansion based upon data up to the early 2000s suggested the carp population may have reached, and was fluctuating around, the ecosystem carrying capacity. It has been widely stated in the scientific literature and media that carp comprise up to 90% of fish biomass in MDB rivers; however, this figure is largely based on sparse data collected in the 1990s and the accuracy of this estimate is uncertain. Here, we analyse three decades (1994–2023) of electrofishing data to estimate the median proportion of total fish biomass contributed by carp across > 1,400 sites in lowland rivers ( 90%) by carp has declined from ≈ 33% of sites in the mid-1990s to ≈ 20% of sites. The proportion of biomass comprised by carp varied depending on the scale of analysis. Across the NSW MDB, carp accounted for a median of 57% (95% CI: 42.5–70.4) of fish biomass at the site level. At the river catchment scale estimates ranged from ≈ 45–66%. In contrast, the median proportion of carp within key rivers ranged from ≈ 46–80%, suggesting that carp can dominate total fish biomass in some rivers for short time-periods. The proportion of biomass contributed by carp at the NSW MDB scale was remarkably stable across decades, suggesting that the carrying capacity of carp may have been reached. Our revised estimates of the contribution of carp to overall fish biomass can facilitate informed debate around the dominance of carp in MDB rivers and provide important information for carp management in the future.

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

The value of adding black carbon to community monitoring of particulate matter - Rebecca A. Sugrue; Chelsea V. Preble; James D.A. Butler; Alaia J. Redon-Gabel; Pietro Marconi; Karan D. Shetty; Lee Ann L. Hill; Audrey M. Amezcua-Smith; Boris R. Lukanov; Thomas W. Kirchstetter (Atmospheric Environment, 2024)

Controls on timescales of soil organic carbon persistence across sub‐Saharan Africa - Sophie F. von Fromm; Sebastian Doetterl; Benjamin M. Butler; Ermias Aynekulu; Asmeret Asefaw Berhe; Stephan M. Haefele; Steve P. McGrath; Keith D. Shepherd; Johan Six; Lulseged Tamene; Ebagnerin J. Tondoh; Tor‐Gunnar Vågen; et al. (Global Change Biology, 2024)
Given the importance of soil for the global carbon cycle, it is essential to understand not only how much carbon soil stores but also how long this carbon persists. Previous studies have shown that the amount and age of soil carbon are strongly affected by the interaction of climate, vegetation, and mineralogy. However, these findings are primarily based on studies from temperate regions and from fine‐scale studies, leaving large knowledge gaps for soils from understudied regions such as sub‐Saharan Africa. In addition, there is a lack of data to validate modeled soil C dynamics at broad scales. Here, we present insights into organic carbon cycling, based on a new broad‐scale radiocarbon and mineral dataset for sub‐Saharan Africa. We found that in moderately weathered soils in seasonal climate zones with poorly crystalline and reactive clay minerals, organic carbon persists longer on average (topsoil: 201 ± 130 years; subsoil: 645 ± 385 years) than in highly weathered soils in humid regions (topsoil: 140 ± 46 years; subsoil: 454 ± 247 years) with less reactive minerals. Soils in arid climate zones (topsoil: 396 ± 339 years; subsoil: 963 ± 669 years) store organic carbon for periods more similar to those in seasonal climate zones, likely reflecting climatic constraints on weathering, carbon inputs and microbial decomposition. These insights into the timescales of organic carbon persistence in soils of sub‐Saharan Africa suggest that a process‐oriented grouping of soils based on pedo‐climatic conditions may be useful to improve predictions of soil responses to climate change at broader scales.

Forecasting suitable areas for wind turbine occurrence to proactively improve wildlife conservation - Matthew A. Boggie; Matthew J. Butler; Steven E. Sesnie; Brian A. Millsap; David R. Stewart; Grant M. Harris; James C. Broska (Journal for Nature Conservation, 2023)

Forester and Logger Response to Emerald Ash Borer in Massachusetts and Vermont: A Secondary Disturbance - Marla Markowski-Lindsay; Paul Catanzaro; Amanda Robillard; Brett J Butler; David A Orwig; Anthony W D’Amato; Jonathan R Thompson; Danelle M Laflower; Meghan Graham MacLean; Malcolm Itter (Journal of Forestry, 2023)
Forester and logger responses to the invasive emerald ash borer (EAB) could substantially affect regions across the United States. We analyzed forester and logger responses to EAB in Massachusetts and Vermont, exploring characteristics associated with purposeful targeting of substantial ash properties; managing forests differently because of EAB; and regeneration goals. One-third of respondents increased timber sales on ash properties, motivated by ecological, not economic, impacts of EAB. Nearly 60% said EAB changed their management activity in stands with ash; changes influenced by the ecological impact of EAB and not economic factors. Those influenced by EAB’s ecological impact to choose properties with substantial ash were more likely to have increased harvest area size, sawtimber removal, and harvest intensity. Loggers were more likely than foresters to remove small-diameter ash and low-grade trees. Both rated regenerating economically valuable species well adapted to the site as their highest essential priority.

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

Correction to: Determining puma habitat suitability in the Eastern USA - Veronica Yovovich; Nathaniel Robinson; Hugh Robinson; Michael J. Manfredo; Shelby Perry; Jeremy T. Bruskotter; John A. Vucetich; Luis Aníbal Solórzano; Lydia A. Roe; Alison Lesure; Jamie Robertson; Tom Butler; et al. (Biodiversity and Conservation, 2023)

Determining puma habitat suitability in the Eastern USA - Veronica Yovovich; Nathaniel Robinson; Hugh Robinson; Michael J. Manfredo; Shelby Perry; Jeremy T. Bruskotter; John A. Vucetich; Luis Aníbal Solórzano; Lydia A. Roe; Alison Lesure; Jamie Robertson; Tom Butler; et al. (Biodiversity and Conservation, 2023)
Pumas ( Puma concolor ) were eliminated from most of the eastern USA a century ago. In the past couple of decades, their recovery in the West has increased puma dispersal into the Midwest, with some individuals even traveling to the East Coast. We combined published expert opinion data and a habitat suitability index in an analysis that identified 17 areas in the Upper Midwest, Ozarks, Appalachia, and New England that could potentially host puma populations in the future. Thirteen of these were larger than 10,000 km 2 and so likely to ensure a puma population’s long-term genetic health. Further, we quantified patch size, human density, livestock density, percent public land, and a sociocultural index reflecting wildlife values for comparing patches, as well as present a summary of current legislation relevant to puma management in the East. Our work may be useful in identifying suitable areas to restore pumas based not only on the quality of their biophysical habitat, but also on social values conducive to puma-human coexistence.

Growth portfolios buffer climate‐linked environmental change in marine systems - Steven E. Campana; Szymon Smoliński; Bryan A. Black; John R. Morrongiello; Stella J. Alexandroff; Carin Andersson; Bjarte Bogstad; Paul G. Butler; Côme Denechaud; David C. Frank; Audrey J. Geffen; Jane Aanestad Godiksen; et al. (Ecology, 2023)
Large‐scale, climate‐induced synchrony in the productivity of fish populations is becoming more pronounced in the world's oceans. As synchrony increases, a population's “portfolio” of responses can be diminished, in turn reducing its resilience to strong perturbation. Here we argue that the costs and benefits of trait synchronization, such as the expression of growth rate, are context dependent. Contrary to prevailing views, synchrony among individuals could actually be beneficial for populations if growth synchrony increases during favorable conditions, and then declines under poor conditions when a broader portfolio of responses could be useful. Importantly, growth synchrony among individuals within populations has seldom been measured, despite well‐documented evidence of synchrony across populations. Here, we used century‐scale time series of annual otolith growth to test for changes in growth synchronization among individuals within multiple populations of a marine keystone species (Atlantic cod, Gadus morhua ). On the basis of 74,662 annual growth increments recorded in 13,749 otoliths, we detected a rising conformity in long‐term growth rates within five northeast Atlantic cod populations in response to both favorable growth conditions and a large‐scale, multidecadal mode of climate variability similar to the East Atlantic Pattern. The within‐population synchrony was distinct from the across‐population synchrony commonly reported for large‐scale environmental drivers. Climate‐linked, among‐individual growth synchrony was also identified in other Northeast Atlantic pelagic, deep‐sea and bivalve species. We hypothesize that growth synchrony in good years and growth asynchrony in poorer years reflects adaptive trait optimization and bet hedging, respectively, that could confer an unexpected, but pervasive and stabilizing, impact on marine population productivity in response to large‐scale environmental change.

Developing a mealybug pheromone monitoring tool to enhance IPM practices in New Zealand vineyards - Nicola J. Sullivan; Vaughn A. Bell; Ruth C. Butler; Roger Wallis; Remya Ramesh; D. Srinivasa Reddy; Andrew M. Twidle; Barry Bunn; C. Rikard Unelius; Lee-Anne M. Manning; David M. Suckling (Journal of Pest Science, 2023)
Mealybugs are phloem-feeding insects found on many crops worldwide. In New Zealand vineyards, they transmit the economically important Grapevine leafroll-associated virus 3 (GLRaV-3). For some mealybug species, synthetic sex pheromones have been commercialised, and are used as monitoring tools. The mealybugs Pseudococcus longispinus and Pseudococcus calceolariae are major pests in many New Zealand vineyards. We present work on the development of a combined P. longispinus and P. calceolariae pheromone lure. The optimal dose for monitoring P. longispinus was found to be 10 µg of the ( S )-(+)-enantiomer, either alone or in the racemic mixture. Addition of the corresponding alcohol did not improve trap catch of P. longispinus . Both the P. longispinus and the P. calceolariae pheromone lures remained active in the field for 90 days. Combining the 2 species’ pheromones had no negative effects on male mealybug trap catch for either species. We conclude that the pheromone ester alone is the best lure for the male P. longispinus . Combining the two mealybug species’ pheromones into a single lure provides the New Zealand viticultural industry with an efficient monitoring tool. Late-vintage deployment of baited lures will provide information on mealybug abundance and local distribution that will inform the scope of future insecticide programmes, to target areas based on need rather than an area-wide application by default.

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

In vivo dissection of Rhoa function in vascular development using zebrafish - Laura M. Pillay; Joseph J. Yano; Andrew E. Davis; Matthew G. Butler; Megan O. Ezeude; Jong S. Park; Keith A. Barnes; Vanessa L. Reyes; Daniel Castranova; Aniket V. Gore; Matthew R. Swift; James R. Iben; et al. (Angiogenesis, 2022)

Characterizing observed surface wind speed in the Hudson Bay and Labrador regions of Canada from an aviation perspective - Andrew C. W. Leung; William A. Gough; Ken A. Butler; Tanzina Mohsin; Micah J. Hewer (International Journal of Biometeorology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Classifying 3-D Models of Coral Reefs Using Structure-From-Motion and Multi-View Semantic Segmentation - Jordan Pierce; Mark J. Butler; Yuri Rzhanov; Kim Lowell; Jennifer A. Dijkstra (Frontiers in Marine Science, 2021)
Benthic quadrat surveys using 2-D images are one of the most common methods of quantifying the composition of coral reef communities, but they and other methods fail to assess changes in species composition as a 3-dimensional system, arguably one of the most important attributes in foundational systems. Structure-from-motion (SfM) algorithms that utilize images collected from various viewpoints to form an accurate 3-D model have become more common among ecologists in recent years. However, there exist few efficient methods that can classify portions of the 3-D model to specific ecological functional groups. This lack of granularity makes it more difficult to identify the class category responsible for changes in the structure of coral reef communities. We present a novel method that can efficiently provide semantic labels of functional groups to 3-D reconstructed models created from commonly used SfM software (i.e., Agisoft Metashape) using fully convolutional networks (FCNs). Unlike other methods, ours involves creating dense labels for each of the images used in the 3-D reconstruction and then reusing the projection matrices created during the SfM process to project semantic labels onto either the point cloud or mesh to create fully classified versions. When quantitatively validating the classification results we found that this method is capable of accurately projecting semantic labels from image-space to model-space with scores as high as 91% pixel accuracy. Furthermore, because each image only needs to be provided with a single set of dense labels this method scales linearly making it useful for large areas or high resolution-models. Although SfM has become widely adopted by ecologists, deep learning presents a steep learning curve for many. To ensure repeatability and ease-of-use, we provide a comprehensive workflow with detailed instructions and open-sourced the programming code to assist others in replicating our methodology. Our method will allow researchers to assess precise changes in 3-D community composition of reef habitats in an entirely novel way, providing more insight into changes in ecological paradigms, such as those that occur during coral-algae shifts.

Hares in the long grass: increased aircraft related mortality of the Irish hare (Lepus timidus hibernicus) over a 30-year period at Ireland’s largest civil airport - Samantha Ball; Fidelma Butler; Anthony Caravaggi; Neil E. Coughlan; Gerry Keogh; Michael J. A. O’Callaghan; Ricky Whelan; Thomas C. Kelly (European Journal of Wildlife Research, 2021)
Collisions between wildlife and aircraft are a serious and growing threat to aviation safety. Understanding the frequency of these collisions, the identity of species involved, and the potential damage that can be inflicted on to aircraft aid mitigation efforts by airfield managers. A record of all animal carcasses recovered from Dublin International Airport, Ireland’s largest civil aviation airport, has been maintained since 1990 where strikes with the endemic Irish hare ( Lepus timidus hibernicus ), a protected subspecies of mountain hare, are of particular concern despite substantial management efforts from the airfield authority. The first strike event with a hare was recorded in 1997, and strike events have substantially increased since then, with a sharp increase recorded in 2011. Over a 30-year period, a total of 320 strike events with the Irish hare have been recorded at the airfield. To date, no strike event with a hare has resulted in damage to an aircraft. However, carcasses can present as a major attraction to avian scavenger species in addition to posing as a risk of causing foreign object damage in the event of an undetected carcass. Hare strikes are discussed in the context of the rate of civil aircraft movements, possible direct and indirect damage to aircraft, and airfield wildlife hazard management. Here, we demonstrate that not only are strike events increasing by 14% on an annual basis, but that the kinetic energy of such an event has the potential to cause significant damage to an aircraft.

Social dynamics of community resilience building in the face of climate change: the case of three Scottish communities - I. Fazey; E. Carmen; H. Ross; J. Rao-Williams; A. Hodgson; B. A. Searle; H. AlWaer; J. O. Kenter; K. Knox; J. R. A. Butler; K. Murray; F. M. Smith; et al. (Sustainability Science, 2021)

Current and future carbon stocks in coastal wetlands within the Great Barrier Reef catchments - Micheli Duarte de Paula Costa; Catherine E. Lovelock; Nathan J. Waltham; Mary Young; Maria F. Adame; Catherine V. Bryant; Don Butler; David Green; Michael A. Rasheed; Cristian Salinas; Oscar Serrano; Paul H. York; et al. (Global Change Biology, 2021)
Australia's Great Barrier Reef (GBR) catchments include some of the world's most intact coastal wetlands comprising diverse mangrove, seagrass and tidal marsh ecosystems. Although these ecosystems are highly efficient at storing carbon in marine sediments, their soil organic carbon (SOC) stocks and the potential changes resulting from climate impacts, including sea level rise are not well understood. For the first time, we estimated SOC stocks and their drivers within the range of coastal wetlands of GBR catchments using boosted regression trees (i.e. a machine learning approach and ensemble method for modelling the relationship between response and explanatory variables) and identified the potential changes in future stocks due to sea level rise. We found levels of SOC stocks of mangrove and seagrass meadows have different drivers, with climatic variables such as temperature, rainfall and solar radiation, showing significant contributions in accounting for variation in SOC stocks in mangroves. In contrast, soil type accounted for most of the variability in seagrass meadows. Total SOC stock in the GBR catchments, including mangroves, seagrass meadows and tidal marshes, is approximately 137 Tg C, which represents 9%–13% of Australia's total SOC stock while encompassing only 4%–6% of the total extent of Australian coastal wetlands. In a global context, this could represent 0.5%–1.4% of global SOC stock. Our study suggests that landward migration due to projected sea level rise has the potential to enhance carbon accumulation with total carbon gains between 0.16 and 0.46 Tg C and provides an opportunity for future restoration to enhance blue carbon.

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Contrasting Futures for Australia’s Fisheries Stocks Under IPCC RCP8.5 Emissions – A Multi-Ecosystem Model Approach - Heidi R. Pethybridge; Elizabeth A. Fulton; Alistair J. Hobday; Julia Blanchard; Catherine M. Bulman; Ian R. Butler; William W. L. Cheung; Leo X. C. Dutra; Rebecca Gorton; Trevor Hutton; Richard Matear; Hector Lozano-Montes; et al. (Frontiers in Marine Science, 2020)

Chromium, manganese, nickel, and cobalt mobility and bioavailability from mafic-to-ultramafic mine spoil weathering in western Massachusetts, USA - Justin A. Mistikawy; Trevor J. Mackowiak; Mark J. Butler; Ivan C. Mischenko; Richard S. Cernak; Justin B. Richardson (Environmental Geochemistry and Health, 2020)

Metal ions and graphene-based compounds as alternative treatment options for burn wounds infected by antibiotic-resistant Pseudomonas aeruginosa - Nathalie Karaky; Andrew Kirby; Andrew J. McBain; Jonathan A. Butler; Mohamed El Mohtadi; Craig E. Banks; Kathryn A. Whitehead (Archives of Microbiology, 2020)
Burn infections caused by Pseudomonas aeruginosa pose a major complication in wound healing. This study aimed to determine the antimicrobial effect of metal ions, graphene (Gr), and graphene oxide (GO), individually and in combination, against the planktonic and biofilm states of two antimicrobially resistant clinical strains of P. aeruginosa each with different antibiotic resistance profiles. Minimum inhibitory, minimum bactericidal, and fractional inhibitory concentrations were performed to determine the efficacy of the metal ions and graphene composites individually and their synergy in combination. Crystal violet biofilm and XTT assays measured the biofilm inhibition and metabolic activity, respectively. Molybdenum, platinum, tin, gold, and palladium ions exhibited the greatest antimicrobial activity (MIC = 7.8–26.0 mg/L), whilst GO and Gr demonstrated moderate-to-no effect against the planktonic bacterial cells, irrespective of their antibiograms. Biofilms were inhibited by zinc, palladium, silver, and graphene. In combination, silver–graphene and molybdenum–graphene inhibited both the planktonic and biofilm forms of the bacteria making them potential candidates for development into topical antimicrobials for burns patients infected with antibiotic-resistant P. aeruginosa .

Robustness of trait connections across environmental gradients and growth forms - Habacuc Flores‐Moreno; Farideh Fazayeli; Arindam Banerjee; Abhirup Datta; Jens Kattge; Ethan E. Butler; Owen K. Atkin; Kirk Wythers; Ming Chen; Madhur Anand; Michael Bahn; Chaeho Byun; et al. (Global Ecology and Biogeography, 2019)
Aim Plant trait databases often contain traits that are correlated, but for whom direct (undirected statistical dependency) and indirect (mediated by other traits) connections may be confounded. The confounding of correlation and connection hinders our understanding of plant strategies, and how these vary among growth forms and climate zones. We identified the direct and indirect connections across plant traits relevant to competition, resource acquisition and reproductive strategies using a global database and explored whether connections within and between traits from different tissue types vary across climates and growth forms. Location Global. Major taxa studied Plants. Time period Present. Methods We used probabilistic graphical models and a database of 10 plant traits (leaf area, specific leaf area, mass‐ and area‐based leaf nitrogen and phosphorous content, leaf life span, plant height, stem specific density and seed mass) with 16,281 records to describe direct and indirect connections across woody and non‐woody plants across tropical, temperate, arid, cold and polar regions. Results Trait networks based on direct connections are sparser than those based on correlations. Land plants had high connectivity across traits within and between tissue types; leaf life span and stem specific density shared direct connections with all other traits. For both growth forms, two groups of traits form modules of more highly connected traits; one related to resource acquisition, the other to plant architecture and reproduction. Woody species had higher trait network modularity in polar compared to temperate and tropical climates, while non‐woody species did not show significant differences in modularity across climate regions. Main conclusions Plant traits are highly connected both within and across tissue types, yet traits segregate into persistent modules of traits. Variation in the modularity of trait networks suggests that trait connectivity is shaped by prevailing environmental conditions and demonstrates that plants of different growth forms use alternative strategies to cope with local conditions.

Application of multi-criteria decision analysis to assess sampling strategies in eutrophic urbanized waterbodies - J. Abbatangelo; A. Byrne; J. F. Butler; J. M. Wilson (Environmental Monitoring and Assessment, 2019)

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

Sublethal effects of natural parasitism act through maternal, but not paternal, reproductive success in a wild population - Olivia Hicks; Jonathan A. Green; Francis Daunt; Emma J. A. Cunningham; Mark Newell; Adam Butler; Sarah J. Burthe (Ecology, 2019)
Parasites are a major component of all animal populations. Males and females often differ in their levels of parasite prevalence, potentially leading to sex differences in the impact of parasitism on fitness, with important implications for the evolution of parasite and host traits including resistance, tolerance, and virulence. However, quantitative measures of the impact of parasitism under free‐living conditions are extremely rare, as they require detailed host demographic data with measures of parasite burden over time. Here, we use endoscopy for direct quantification of natural‐parasite burdens and relate these to reproductive success over 7 yr in a wild population of seabirds. Contrary to predictions, only female burdens were associated with negative impacts of parasitism on breeding success, despite males having significantly higher burdens. Female reproductive success declined by 30% across the range of natural parasite burdens. These effects persisted when accounting for interannual population differences in breeding success. Our results provide quantitative estimates of profound sub‐lethal effects of parasitism on the population. Importantly, they highlight how parasites act unpredictably to shape ecological and evolutionary processes in different components of the same population, with implications for demography and selection on host and parasite traits.

Quantitation of Purines from Pigeon Guano and Implications for Cryptococcus neoformans Survival During Infection - Jessica L. Chitty; David J. Edwards; Avril A. B. Robertson; Mark S. Butler; John A. Duley; Matthew A. Cooper; James A. Fraser (Mycopathologia, 2019)

Small-Area Family Forest Ownerships in the USA - Stephanie A. Snyder; Brett J. Butler; Marla Markowski-Lindsay (Small-scale Forestry, 2019)

Correction to: Pronounced long-term trends in year-round diet composition of the European shag Phalacrocorax aristotelis - Richard J. Howells; Sarah J. Burthe; Jonathan A. Green; Michael P. Harris; Mark A. Newell; Adam Butler; Sarah Wanless; Francis Daunt (Marine Biology, 2019)

Does fish herding enhance catch rates and detection of invasive bigheaded carp? - Steven E. Butler; Anthony P. Porreca; Scott F. Collins; Jonathan A. Freedman; Joseph J. Parkos; Matthew J. Diana; David H. Wahl (Biological Invasions, 2019)

Pronounced long-term trends in year-round diet composition of the European shag Phalacrocorax aristotelis - Richard J. Howells; Sarah J. Burthe; Jonathan A. Green; Michael P. Harris; Mark A. Newell; Adam Butler; Sarah Wanless; Francis Daunt (Marine Biology, 2018)

Chromatographic fingerprinting of Lupinus luteus L. (Leguminosae) main secondary metabolites: a case of domestication affecting crop variability - Claudia E. Osorio; Veronique S. E. Amiard; Javiera Aravena-Calvo; Joshua A. Udall; Jeff J. Doyle; Iván J. Maureira-Butler (Genetic Resources and Crop Evolution, 2018)

Global biodiversity research tied up by juridical interpretations of access and benefit sharing - D. Neumann; A. V. Borisenko; J. A. Coddington; C. L. Häuser; C. R. Butler; A. Casino; J. C. Vogel; G. Haszprunar; P. Giere (Organisms Diversity & Evolution, 2018)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Development and testing of a micro wind tunnel for on-site wind erosion simulations - Craig L. Strong; John F. Leys; Mike R. Raupach; Joanna E. Bullard; Hélène A. Aubault; Harry J. Butler; Grant H. McTainsh (Environmental Fluid Mechanics, 2016)

Anatomy and lateralization of the human corticobulbar tracts: an fMRI-guided tractography study - Frédérique J. Liégeois; James Butler; Angela T. Morgan; Jonathan D. Clayden; Chris A. Clark (Brain Structure and Function, 2016)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Family Forest Owners’ Perceptions of Landowner Assistance Programs in the USA: A Qualitative Exploration of Program Impacts on Behaviour - Kyle Andrejczyk; Brett J. Butler; Brenton J. Dickinson; Jaketon H. Hewes; Marla Markowski-Lindsay; David B. Kittredge; Michael A. Kilgore; Stephanie A. Snyder; Paul F. Catanzaro (Small-scale Forestry, 2016)

Bench-Scale and Pilot-Scale Treatment Technologies for the Removal of Total Dissolved Solids from Coal Mine Water: A Review - Patricio X. Pinto; Souhail R. Al-Abed; David A. Balz; Barbara A. Butler; Ronald B. Landy; Samantha J. Smith (Mine Water and the Environment, 2016)

Trends in marine climate change research in the Nordic region since the first IPCC report - M. W. Pedersen; A. Kokkalis; H. Bardarson; S. Bonanomi; W. J. Boonstra; W. E. Butler; F. K. Diekert; N. Fouzai; M. Holma; R. E. Holt; K. Ø. Kvile; E. Nieminen; et al. (Climatic Change, 2016)

Integrating Top-Down and Bottom-Up Adaptation Planning to Build Adaptive Capacity: A Structured Learning Approach - J. R. A. Butler; R. M. Wise; T. D. Skewes; E. L. Bohensky; N. Peterson; W. Suadnya; Y. Yanuartati; T. Handayani; P. Habibi; K. Puspadi; N. Bou; D. Vaghelo; et al. (Coastal Management, 2015)

Age and growth of mangrove red snapper Lutjanus argentimaculatus at its cool‐water‐range limits - T. P. Piddocke; G. L. Butler; P. A. Butcher; J. Stewart; D. J. Bucher; L. Christidis (Journal of Fish Biology, 2015)
This study investigates the age and growth of Lutjanus argentimaculatus at its southern (cooler) range limits in eastern Australia. Specimens were collected from New South Wales and southern Queensland between November 2011 and December 2013. Fork lengths ( L F ) ranged from 190 to 1019 mm, and ages ranged from 2+ to 57+ years. Growth was described by the von Bertalanffy growth function with coefficients L ∞ = 874·92 mm, K = 0·087 year −1 and t 0 = −2·76 years. Estimates of the instantaneous natural mortality rate ( M ) ranged from 0·072 to 0·25. The L F (mm) and mass ( W ; g) relationship was represented by the equation: . The maximum age of 57+ years is the oldest reported for any lutjanid and comparisons with tropical studies suggest that the age‐based demography of L. argentimaculatus follows a latitudinal gradient. High maximum ages and low natural mortality rates indicate considerable vulnerability to overexploitation at the species' cool‐water‐range limits. These results demonstrate the need to identify underlying processes driving latitudinal gradients in fish demography.

Association between high-sensitivity C-reactive protein (hsCRP) and change in mammographic density over time in the SWAN mammographic density subcohort - Kunlanat Makboon; Ellen B. Gold; Danielle J. Harvey; Lesley M. Butler; Laurel A. Habel (Cancer Causes & Control, 2015)

Scaffolds for Tendon and Ligament Repair and Regeneration - Anthony Ratcliffe; David L. Butler; Nathaniel A. Dyment; Paul J. Cagle; Christopher S. Proctor; Seena S. Ratcliffe; Evan L. Flatow (Annals of Biomedical Engineering, 2015)

Atlantic bluefin tuna Thunnus thynnus feeding ecology in the northern Gulf of Mexico: a preliminary description of diet from the western Atlantic spawning grounds - C. M. Butler; J. M. Logan; J. M. Provaznik; E. R. Hoffmayer; M. D. Staudinger; J. M. Quattro; M. A. Roberts; G. W. Ingram; A. G. Pollack; M. E. Lutcavage (Journal of Fish Biology, 2015)
A combination of stomach contents, nitrogen stable‐isotope and tissue C:N values are presented to demonstrate feeding activity of Atlantic bluefin tuna Thunnus thynnus on the Gulf of Mexico (GOMEX) spawning grounds. Diets include teleosts, cephalopods, crustaceans and a pelagic tunicate ( Pyrosoma atlanticum ). Results reveal the need to classify the GOMEX as a T. thynnus feeding ground.

Application of stable isotope mixing models for defining trophic biomagnification pathways of mercury and selenium - H. J. Jones; K. M. Swadling; E. C. V. Butler; L. A. Barry; C. K. Macleod (Limnology and Oceanography, 2014)
Trophic models based on nitrogen stable isotope ratios ( δ 15 N) have been shown to predict changes in mercury (Hg) concentrations in fish; however, they are usually applied at the ecosystem scale and are rarely directed at known trophic pathways. We discuss a novel approach in which we combined gut contents analysis and stable isotope analyses ( δ 15 N and δ 13 C) into a Bayesian isotopic mixing model to provide a quantitative estimate of Hg and selenium (Se) biomagnification in an estuarine food web. Estimates of the relationship between total mercury (THg) and methylmercury (MeHg) were significantly improved in mixing model‐adjusted food webs over models that included all known prey sources. Spatial differences in dietary composition and MeHg bioavailability offer strong evidence that local food webs can have a significant effect on the biomagnification of Hg within benthic fish species. While no evidence of Se biomagnification was found, lower Se : Hg ratios at higher trophic levels could be attributed to increasing trophic Hg concentration. Furthermore, stable isotope analysis suggested Hg and Se biotransfer from benthic sources to fish. Overall, the findings highlight that isotope mixing models can be a significant aid in assessments of contaminant biomagnification, particularly when it is important to define food pathways to top predators.

Changes in extreme temperature and precipitation in the Caribbean region, 1961–2010 - Tannecia S. Stephenson; Lucie A. Vincent; Theodore Allen; Cedric J. Van Meerbeeck; Natalie McLean; Thomas C. Peterson; Michael A. Taylor; Arlene P. Aaron‐Morrison; Thomas Auguste; Didier Bernard; Joffrey R. I. Boekhoudt; Rosalind C. Blenman; et al. (International Journal of Climatology, 2014)

Larval Distribution and Behavior of Chrysomya rufifacies (Macquart) (Diptera: Calliphoridae) Relative to Other Species on Florida Black Bear (Carnivora: Ursidae) Decomposing Carcasses - S L Swiger; J A Hogsette; J F Butler (Neotropical Entomology, 2014)

Effect of β3 adrenoceptor activation in the basolateral amygdala on ethanol seeking behaviors - T. R. Butler; A. M. Chappell; J. L. Weiner (Psychopharmacology, 2014)

Recent environmental change and trace metal pollution in World Heritage Bathurst Harbour, southwest Tasmania, Australia - Krystyna M. Saunders; Jennifer J. Harrison; Edward C. V. Butler; Dominic A. Hodgson; Andrew McMinn (Journal of Paleolimnology, 2013)

Joint effects between five identified risk variants, allergy, and autoimmune conditions on glioma risk - Mahboobeh Safaeian; Preetha Rajaraman; Patricia Hartge; Meredith Yeager; Martha Linet; Mary Ann Butler; Avima M. Ruder; Mark P. Purdue; Ann Hsing; Laura Beane-Freeman; Jane A. Hoppin; Demetrius Albanes; et al. (Cancer Causes & Control, 2013)

Soil organic carbon dust emission: an omitted global source of atmospheric CO 2 - Adrian Chappell; Nicholas P. Webb; Harry J. Butler; Craig L. Strong; Grant H. McTainsh; John F. Leys; Raphael A. Viscarra Rossel (Global Change Biology, 2013)
Soil erosion redistributes soil organic carbon ( SOC ) within terrestrial ecosystems, to the atmosphere and oceans. Dust export is an essential component of the carbon (C) and carbon dioxide ( CO 2 ) budget because wind erosion contributes to the C cycle by removing selectively SOC from vast areas and transporting C dust quickly offshore; augmenting the net loss of C from terrestrial systems. However, the contribution of wind erosion to rates of C release and sequestration is poorly understood. Here, we describe how SOC dust emission is omitted from national C accounting, is an underestimated source of CO 2 and may accelerate SOC decomposition. Similarly, long dust residence times in the unshielded atmospheric environment may considerably increase CO 2 emission. We developed a first approximation to SOC enrichment for a well‐established dust emission model and quantified SOC dust emission for Australia (5.83 Tg CO 2 ‐e yr −1 ) and Australian agricultural soils (0.4 Tg CO 2 ‐e yr −1 ). These amount to underestimates for CO 2 emissions of ≈10% from combined C pools in Australia (year = 2000), ≈5% from Australian Rangelands and ≈3% of Australian Agricultural Soils by Kyoto Accounting. Northern hemisphere countries with greater dust emission than Australia are also likely to have much larger SOC dust emission. Therefore, omission of SOC dust emission likely represents a considerable underestimate from those nations’ C accounts. We suggest that the omission of SOC dust emission from C cycling and C accounting is a significant global source of uncertainty. Tracing the fate of wind‐eroded SOC in the dust cycle is therefore essential to quantify the release of CO 2 from SOC dust to the atmosphere and the contribution of SOC deposition to downwind C sinks.

Skeletal muscle adaptations to physical inactivity and subsequent retraining in young men - E. L. Campbell; O. R. Seynnes; R. Bottinelli; J. S. McPhee; P. J. Atherton; D. A. Jones; G. Butler-Browne; M. V. Narici (Biogerontology, 2013)

Effect of Potassium and Nitrogen Fertilizer on Switchgrass Productivity and Nutrient Removal Rates under Two Harvest Systems on a Low Potassium Soil - Maru K. Kering; Twain J. Butler; Jon T. Biermacher; Jagadeesh Mosali; John A. Guretzky (BioEnergy Research, 2013)

Switchgrass Biomass and Nitrogen Yield with Over-Seeded Cool-season Forages in the Southern Great Plains - Twain J. Butler; James P. Muir; Chengjun Huo; John A. Guretzky (BioEnergy Research, 2013)

Linkage haplotype for allotypic variants of porcine IgA and IgG subclass genes - A. Kloep; N. Wertz; M. Mendicino; J. Ramsoondar; J. E. Butler (Immunogenetics, 2012)

Response of Female Frankliniella occidentalis (Pergande) to Visual Cues and Para-anisaldehyde in a Flight Chamber - Melanie M. Davidson; Ruth C. Butler; David A. J. Teulon (Journal of Insect Behavior, 2012)

Relative humidity at Armagh Observatory, 1838–2008 - C. J. Butler; A. M. García‐Suárez (International Journal of Climatology, 2012)
We present a calibrated atmospheric humidity series for Armagh Observatory, Northern Ireland. Beginning in 1838 and continuing to the present day, this series is believed to be the longest presented so far. Daily wet‐bulb and dry‐bulb temperature readings are corrected for the time of reading and for known instrumental errors to determine mean monthly, seasonal and annual relative humidity (RH) at 09:00 GMT from 1838 to 2008 and at 21:00 GMT from 1844 to 1964. The mean seasonal and annual time series of RH at this site show only marginal evidence for a trend in RH since the 1880s, however, there is significant decadal and multi‐decadal variability, some of which appears to be cyclic. Wavelet analysis indicates the presence of two quasi‐periodic components in RH, one ranging from 23.4 to 25.5 years and the other from 36 to 51 years. We discuss potential physical origins of these cycles such as changes in the atmospheric and thermohaline circulation and the solar magnetic cycle. There is a small but significant anti‐correlation between RH and northerly winds. Two conspicuous peaks in RH during the 19th century coincide with major infestations of potato blight in Ireland. Copyright © 2011 Royal Meteorological Society

Soil warming alters nitrogen cycling in a New England forest: implications for ecosystem function and structure - S. M. Butler; J. M. Melillo; J. E. Johnson; J. Mohan; P. A. Steudler; H. Lux; E. Burrows; R. M. Smith; C. L. Vario; L. Scott; T. D. Hill; N. Aponte; et al. (Oecologia, 2012)

Prostate Cancer Knowledge in Irish Men - Rowan G. Casey; David J. Rea; Ted McDermott; Ronald Grainger; Michael Butler; J. A. Thornhill (Journal of Cancer Education, 2012)

Biomass Yield and Nutrient Responses of Switchgrass to Phosphorus Application - M. K. Kering; J. T. Biermacher; T. J. Butler; J. Mosali; J. A. Guretzky (BioEnergy Research, 2012)

Biomass Yield and Nutrient Removal Rates of Perennial Grasses under Nitrogen Fertilization - M. K. Kering; T. J. Butler; J. T. Biermacher; J. A. Guretzky (BioEnergy Research, 2012)

Indications of phenotypic plasticity in moulting birds: captive geese reveal adaptive changes in mineralisation of their long bones during wing moult - Steven J. Portugal; Patrick J. Butler; Jonathan A. Green; Phillip Cassey (Journal of Ornithology, 2011)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Generation of antibody- and B cell-deficient pigs by targeted disruption of the J-region gene segment of the heavy chain locus - M. Mendicino; J. Ramsoondar; C. Phelps; T. Vaught; S. Ball; T. LeRoith; J. Monahan; S. Chen; A. Dandro; J. Boone; P. Jobst; A. Vance; et al. (Transgenic Research, 2011)

Targeted disruption of the porcine immunoglobulin kappa light chain locus - J. Ramsoondar; M. Mendicino; C. Phelps; T. Vaught; S. Ball; J. Monahan; S. Chen; A. Dandro; J. Boone; P. Jobst; A. Vance; N. Wertz; et al. (Transgenic Research, 2011)

Leptidea sinapis (Wood White butterfly) egg-laying habitat and adult dispersal studies in Herefordshire - S. A. Clarke; D. G. Green; J. Joy; K. Wollen; I. Butler (Journal of Insect Conservation, 2011)

Association of common DNA sequence variants at 33 genetic loci with blood lipids in individuals of African ancestry from Jamaica - R. Gupta; K. Ejebe; J. Butler; G. Lettre; H. Lyon; C. Guiducci; R. Wilks; F. Bennett; T. Forrester; B. Tayo; K. Musunuru; J. Hirschhorn; et al. (Human Genetics, 2010)

Recommendation of short tandem repeat profiling for authenticating human cell lines, stem cells, and tissues - Rita Barallon; Steven R. Bauer; John Butler; Amanda Capes-Davis; Wilhelm G. Dirks; Eugene Elmore; Manohar Furtado; Margaret C. Kline; Arihiro Kohara; Georgyi V. Los; Roderick A. F. MacLeod; John R. W. Masters; et al. (In Vitro Cellular & Developmental Biology - Animal, 2010)

A novel method for quantifying the glossiness of animals - Matthew B. Toomey; Michael W. Butler; Melissa G. Meadows; Lisa A. Taylor; H. Bobby Fokidis; Kevin J. McGraw (Behavioral Ecology and Sociobiology, 2010)

Improving the Performance of the Roundtable on Sustainable Palm Oil for Nature Conservation - WILLIAM F. LAURANCE; LIAN P. KOH; RHETT BUTLER; NAVJOT S. SODHI; COREY J. A. BRADSHAW; J. DAVID NEIDEL; HAZEL CONSUNJI; JAVIER MATEO VEGA (Conservation Biology, 2010)

Active, but not passive cigarette smoking was inversely associated with mammographic density - Lesley M. Butler; Ellen B. Gold; Shannon M. Conroy; Carolyn J. Crandall; Gail A. Greendale; Nina Oestreicher; Charles P. Quesenberry; Laurel A. Habel (Cancer Causes & Control, 2010)

Analysis of flow processes in fractured chalk under pumped and ambient conditions (UK) - A. P. Butler; S. A. Mathias; A. J. Gallagher; D. W. Peach; A. T. Williams (Hydrogeology Journal, 2009)

Siderophores of Marinobacter aquaeolei: petrobactin and its sulfonated derivatives - Vanessa V. Homann; Katrina J. Edwards; Eric A. Webb; Alison Butler (BioMetals, 2009)

Thinking and managing outside the box: coalescing connectivity networks to build region-wide resilience in coral reef ecosystems - R. S. Steneck; C. B. Paris; S. N. Arnold; M. C. Ablan-Lagman; A. C. Alcala; M. J. Butler; L. J. McCook; G. R. Russ; P. F. Sale (Coral Reefs, 2009)

Metallothionein Treatment Attenuates Microglial Activation and Expression of Neurotoxic Quinolinic Acid Following Traumatic Brain Injury - R. S. Chung; Y. K. Leung; C. W. Butler; Y. Chen; E. D. Eaton; M. W. Pankhurst; A. K. West; G. J. Guillemin (Neurotoxicity Research, 2009)

Tracking macaroni penguins during long foraging trips using ‘behavioural geolocation’ - Jonathan A. Green; Rory P. Wilson; Ian L. Boyd; Anthony J. Woakes; Chris J. Green; Patrick J. Butler (Polar Biology, 2009)

Is seagrass an important nursery habitat for the Caribbean spiny lobster, panulirus argus , in Florida? - Donald C. Behringer; Mark J. Butler; William F. Herrnkind; John H. Hunt; Charles A. Acosta; William C. Sharp (New Zealand Journal of Marine and Freshwater Research, 2009)
Caribbean spiny lobster (Panulirus argus) settle preferentially in macroalgal‐covered hard‐bottom habitat, but seagrass is more prevalent in Florida (United States) and the Caribbean, so even low settlement of lobsters within seagrass could contribute substantially to recruitment if post‐settlement survival and growth were high. We tested the role of seagrass and hard‐bottom habitats for P. argus recruitment in three ways. We first explored possible density‐dependent regulation of early benthic juvenile lobster survival within cages deployed in seagrass and hard‐bottom habitats. Second, we compared settlement and survival of P. argus in both habitats, by comparing the recovery of microwire‐tagged early benthic juveniles from patches of seagrass and hard‐bottom. Finally, we assessed the relative abundance of juvenile lobsters in each habitat by deploying artificial structures in seagrass sites and compared these data with data from similar deployments of artificial structures in hard‐bottom habitat in other years. More early benthic juvenile lobsters were recovered from cages placed in hard‐bottom than in seagrass, but mortality of the early benthic life stage was high in both habitats. In regional surveys, the mean number of lobsters recovered from artificial shelters deployed within seagrass was lower than in any year that we sampled hard‐bottom, indicating that fewer lobsters reside naturally in seagrass, particularly large juveniles >40 mm carapace length. The greater abundance (and likely survival) of juvenile P. argus that we observed in hard‐bottom habitat as opposed to seagrass, combined with previous studies demonstrating that postlarval P. argus are attracted to, settle in, and metamorphose more quickly in red macroalgae, confirm that macroalgae‐dominated hard‐bottom habitat appears to be the preferred and more optimal nursery for Caribbean spiny lobster.

Relationships of red-cockaded woodpecker reproduction and foraging habitat characteristics in Arkansas and Louisiana - Matthew J. Butler; Philip A. Tappe (European Journal of Wildlife Research, 2008)

A quantitative comparison of the commonly used methods for extracting carotenoids from avian plasma - Kevin J. McGraw; Elizabeth A. Tourville; Michael W. Butler (Behavioral Ecology and Sociobiology, 2008)

A Greenhouse Assay for Powdery Scab (Spongospora subterranea f. sp. subterranea) Resistance in Potato - S. J. Baldwin; R. A. Genet; R. C. Butler; J. M. E. Jacobs (Potato Research, 2008)

Analyses of a multi-parent population derived from two diverse alfalfa germplasms: testcross evaluations and phenotype–DNA associations - I. J. Maureira-Butler; J. A. Udall; T. C. Osborn (Theoretical and Applied Genetics, 2007)

Visual cortex activation in kinesthetic guidance of reaching - W. G. Darling; R. J. Seitz; S. Peltier; L. Tellmann; A. J. Butler (Experimental Brain Research, 2007)

Transgenic Potato Lines Expressing cry1Ba1 or cry1Ca5 Genes are Resistant to Potato Tuber Moth - S. Meiyalaghan; J. M. E. Jacobs; R. C. Butler; S. D. Wratten; A. J. Conner (Potato Research, 2007)

Modelling the impacts of removing seal predation from Atlantic salmon, Salmo salar , rivers in Scotland: a tool for targeting conflict resolution - J. R. A. BUTLER; S. J. MIDDLEMAS; I. M. GRAHAM; P. M. THOMPSON; J. D. ARMSTRONG (Fisheries Management and Ecology, 2006)
Bioenergetics were used to model the potential impacts on adult Atlantic salmon, Salmo salar L., stocks and rod fisheries of removing harbour seals, Phoca vitulina L., from three rivers of different scales in the Moray Firth, Scotland, viz: the Spey (large), Conon (medium) and Moriston (small). Overall, seals had the greatest impact on the Moriston, where removal of a single animal could increase cumulative catch by 17% during the fishing season. On the Conon and Spey the impacts were negligible, and resulted in increased catches of 33% in rivers with monthly rod catches ≤10 fish, but declined to 34 fish. The outputs of the models are qualitative, but provide a management tool for targeting action to resolve seal‐salmon fishery conflict. Smaller salmon population units, and spring salmon sub‐stocks and fisheries in particular, are most vulnerable to predation. The merit of this approach is discussed regarding the management of Special Areas of Conservation for salmon and seals.

Soil temperatures at Armagh Observatory, Northern Ireland, from 1904 to 2002 - A. M. García-Suárez; C. J. Butler (International Journal of Climatology, 2006)

Accounting for body condition improves allometric estimates of resting metabolic rates in fasting king penguins, Aptenodytes patagonicus - A. Fahlman; L. G. Halsey; P. J. Butler; D.R. Jones; A. Schmidt; S. Durand; G. Froget; C. -A. Bost; A. J. Woakes; C. Duchamp; Y. Handrich (Polar Biology, 2006)

The N-terminus of Himar1 mariner transposase mediates multiple activities during transposition - Matthew G. Butler; Sangita A. Chakraborty; David J. Lampe (Genetica, 2006)

Free-range Village Chickens on the Accra Plains, Ghana:Their Husbandry and Productivity - P. A. T. Aboe; K. Boa-Amponsem; S. A. Okantah; E. A. Butler; P. T. Dorward; M. J. Bryant (Tropical Animal Health and Production, 2006)

Air temperatures at Armagh Observatory, Northern Ireland, from 1796 to 2002 - C. J. Butler; A. M. García Suárez; A. D. S. Coughlin; C. Morrell (International Journal of Climatology, 2005)
Three independent mean temperature series for Armagh Observatory, covering the period 1796–2002 have been calibrated and corrected for the time of reading and exposure. Agreement between the three series is good in regions of overlap. With a short gap in the Armagh data from 1825 to 1833 filled by data from two stations in Dublin, the resulting series is the longest for the island of Ireland and one of the longest for any single site in the British Isles. Over the past 207 years, we note that temperatures in Armagh, in all seasons, show a gradual overall trend upwards. However, there are seasonal differences: summer and spring temperatures have increased by only half as much as those in autumn and winter. This is partly due to the exceptionally cold winters and autumns experienced prior to 1820. Relative to the overall trend, warm periods occurred in Ireland, as in other parts of Europe, in the mid‐19th century, in the mid‐20th century and at the end of the 20th century. Relatively cool temperatures prevailed in the early 19th century, in the 1880s and in the 1970s. Thus, if the baseline against which current temperatures are compared were moved from the late 19th century to include the earlier warm period, the apparent warming at the end of the late 20th century would be correspondingly reduced. A gradual decline in the daily temperature range at Armagh since 1844 may have resulted from higher minimum temperatures associated with increased cloudiness. A 7.8 year periodicity is identified in winter and spring mean temperatures at Armagh, which is probably a consequence of the North Atlantic oscillation. Copyright © 2005 Royal Meteorological Society

The prevalence of escaped farmed salmon, Salmo salar L., in the River Ewe, western Scotland, with notes on their ages, weights and spawning distribution - J. R. A. BUTLER; P. D. CUNNINGHAM; K. STARR (Fisheries Management and Ecology, 2005)
The prevalence of escaped farmed Atlantic salmon, Salmo salar L., in the River Ewe, western Scotland, was assessed. After the establishment of smolt cages in the catchment and marine cages near the river mouth during 1986–1987, approximately 425 000 parr and smolts, and 122 000 growers have escaped. Between 1987 and 2001, farmed salmon occurred in the rod fishery in 13 of the 15 years, contributing at least 5.8% of the total catch, with a maximum annual frequency of 27.1%. It was estimated that P

Assessment of genetic diversity in isolates of Ciborinia camelliae Kohn from New Zealand and the United States of America - R. F. van Toor; H. J. Ridgway; R. C. Butler; M. V. Jaspers; A. Stewart (Australasian Plant Pathology, 2005)

Comparative In Vitro Surveillance of Amoxicillin-Clavulanic Acid and Four Oral Comparators Against 21,232 Clinical Isolates from Europe - D. J. Hoban; S. K. Bouchillon; J. L. Johnson; G. G. Zhanel; D. L. Butler; K. A. Saunders; L. A. Miller; J. A. Poupard (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Weak correspondence between macroinvertebrate assemblages and land use in Prairie Pothole Region wetlands, USA - Brian A. Tangen; Malcolm G. Butler; Michael J. Ell (Wetlands, 2003)

Buccal cells as a source of DNA for comparative animal genomic analysis - R. Brooks; J. Williamson; A. Hensley; E. Butler; G. Touchton; E. Smith (Biotechnology Letters, 2003)

A comparison of horizontally and vertically deployed aquatic invertebrate activity traps - Miles J. Muscha; Kyle D. Zimmer; Malcolm G. Butler; Mark A. Hanson (Wetlands, 2001)

Fitting fertilisation kinetics models for free-spawning marine invertebrates - C. A. Styan; A. J. Butler (Marine Biology, 2000)

A direct regional scale estimate of transgene movement from genetically modified oilseed rape to its wild progenitors - M. J. Wilkinson; I. J. Davenport; Y. M. Charters; A. E. Jones; J. Allainguillaume; H. T. Butler; D. C. Mason; A. F. Raybould (Molecular Ecology, 2000)
One of the major environmental concerns over genetically modified (GM) crops relates to transgene movement into wild relatives. The pattern of hybridization ultimately affects the scale and rapidity of ecological change and the feasibility of containment. A new procedure for quantifying hybrid formation over large areas is described. Remote sensing was used to identify possible sites of sympatry between Brassica napus and its progenitor species across 15 000 km 2 of south‐east England in 1998. Two sympatric populations with B. rapa and one with B. oleracea were found over the entire survey area. Every newly recruited plant in these populations in 1999 was screened for hybrid status using flow cytometry and molecular analyses. One hybrid was observed from the 505 plants screened in the B. rapa populations but none of the nine B. oleracea recruits were hybrids. Measures to minimize gene flow are suggested, and a procedure for the post‐release evaluation and containment of GM cultivars is proposed.

Zotepine in the prevention of recurrence: a randomised, double-blind, placebo-controlled study for chronic schizophrenia - S.J. Cooper; A. Butler; J. Tweed; C. Welch; J. Raniwalla (Psychopharmacology, 2000)

Current and elevated levels of UV‐B radiation have few impacts on yields of perennial forage crops - Yousef A. Papadopoulos; Robert J. Gordon; Kenneth B. Mcrae; RoY. S. Bush; Gilles Bélanger; E. AnnE. Butler; Sherry A. E. Fillmore; Malcolm Morrison (Global Change Biology, 1999)
Summary Two experiments assessed the effect of current and elevated levels of ultraviolet B (UV‐B) radiation on forage crop production. The effect of current levels of UV‐B radiation was assessed by comparing the growth of eight cultivars of four legume and four grass species for three growing seasons (1994–96) under simulated sward conditions in the field. An exclusion system using cellulose diacetate or polyester covers provided comparable growing conditions for the plants, except for the presence or absence of ambient UV‐B radiation, respectively. The second experiment studied the effect of elevated levels of UV‐B on eight cultivars of two legume and two grass species in the greenhouse under simulated sward conditions. Natural lighting with sufficient supplemental light was used to provide ideal growing conditions for a 16‐h day length. Separate sets of UV lights were installed to provide UV‐B levels at approximately the same intensity as would be found in mid summer, and 33% and 66% more than this value. A fourth treatment consisted of removing UV‐B radiation by using a polyester filter. Plant production was measured in both experiments. In 1994, field herbage yields from all young grass and legume seedlings were not significantly affected by the exclusion of ambient UV‐B radiation, with the exception of alfalfa. Intra‐specific variations with alfalfa yields were found for reduced levels of UV‐B radiation. In general, these trends persisted as stands matured during two post seeding years. In the second experiment, no significant differences were observed for all tested species with increasing levels of UV‐B radiation, except with some alfalfa cultivars and one birdsfoot trefoil cultivar. Collectively, these results demonstrate that in the northern latitudes young and mature plants of the studied species are resistant to current and potentially higher levels of solar UV‐B radiation, with the exception of some alfalfa cultivars. The yield of these cultivars increased under enhanced levels of UV‐B radiation in the greenhouse and decreased when UV‐B was excluded in the field.

Sperm economy and limitation in spiny lobsters - A. B. MacDiarmid; Mark J. Butler IV (Behavioral Ecology and Sociobiology, 1999)

Adaptive strategies that reduce predation on Caribbean spiny lobster postlarvae during onshore transport - Charles A. Acosta; Mark J. Butler (Limnology and Oceanography, 1999)
Like many marine species with meroplanktonic larvae, the Caribbean spiny lobster ( Panulirus argus ) has a postlarval stage that moves from the oceanic plankton to inshore nurseries only under specific environmental conditions (i.e., at night, in the surface water layer, on the flood tide, and during new moon), presumably to avoid predation or to enhance onshore transport. Using field and mesocosm experiments, we compared predation on planktonic postlarvae swimming at night near the surface and bottom over coastal habitats along typical offshore–inshore transport paths and determined whether predation rates differed between lunar periods (new moon vs. full moon) and with prey density (i.e., predator encounter rates). We also measured predation on transparent (newly settled) and pigmented (nearing metamorphosis) postlarvae sheltering in coral reef, seagrass, and macroalgal habitats during the day. We measured predation on postlarvae swimming near the surface and bottom along typical offshore–inshore transport paths (i.e., coral reefs, coastal lagoon, and bay) by tethering postlarvae to floats that drifted on the nightly flood tide during new moon. To test the hypothesis that new‐moon transport of postlarvae may have evolved as a means to avoid higher predation under the bright full moon, we repeated the pelagic tethering experiments at the reef and in the bay during full moon. Mortality was highest over coral reefs regardless of lunar phase, but it was lower nearshore, especially in the bay near the surface and during new moon. Predation on benthic, recently settled transparent postlarvae and pigmented postlarvae (nearing metamorphosis) was also higher when tethered on the reef as opposed to vegetated habitats in the lagoon and bay. In experimental mesocosms, planktivorous fish were equally efficient at consuming postlarvae under new‐ and full‐moon conditions when postlarval density was high, as it is in the constricted water column over the reefs. However, when postlarvae were less dense, mortality was significantly lower during new moon. Collectively, these results indicate that several behavioral traits exhibited by postlarval spiny lobsters, including inshore migration during the darkest lunar phase, use of surface waters, and settlement in vegetated habitats, reduce their risk of predation, particularly in the shallow bay. No single behavioral strategy is universally advantageous across all coastal habitats, but combined, they are an effective means to reduce predation across heterogeneous environments that postlarvae must transit during recruitment.

Regional distribution of metallothionein and zinc in the mouse gut - C. D. Tran; R. N. Butler; J. C. Philcox; A. M. Rofe; G. S. Howarth; P. Coyle (Biological Trace Element Research, 1998)

Epidemiology of communicable disease in small populations - Christopher J. Rhodes; A. R. Butler; Roy M. Anderson (Journal of Molecular Medicine, 1998)

Construction of an RFLP linkage map for cultivated sunflower - C. C. Jan; B. A. Vick; J. F. Miller; A. L. Kahler; E. T. Butler III. (Theoretical and Applied Genetics, 1998)

Mapping of the gene encoding the B56β subunit of protein phosphatase 2A (PPP2R5B) to a 0.5-Mb region of chromosome 11q13 and its exclusion as a candidate gene for multiple endocrine neoplasia type 1 (MEN1) - S. A. Forbes; A. A. J. Pannett; J. H. D. Bassett; B. Harding; C. Wooding; R. V. Thakker; R. Butler; D. Ogilvie; R. Anand; P. Gaudray; G. Weber; C. Larsson; et al. (Human Genetics, 1997)

Temporal patterns and transport processes in recruitment of spiny lobster ( Panulirus argus ) postlarvae to south Florida - C. A. Acosta; T. R. Matthews; M. J. Butler IV. (Marine Biology, 1997)

Condensed tannins in Leucaena and their relation to psyllid resistance - R. A. Wheeler; W. R. Chaney; L. G. Butler; J. L. Brewbaker (Agroforestry Systems, 1994)

Some properties of adenylate kinase from chemolithotrophically grown Thiobacillus novellus - I. R. C. McKellar; A. M. Charles; B. J. Butler (Archives of Microbiology, 1980)

s of papers presented at the Forty-First annual meeting - R. E. Anderson; A. P. Benson; W. J. Hooker; Gerard S. Birth; Karl H. Norris; Reiner Bonde; Robert Akeley; Donald Merriam; C. C. Craft; H. W. Siegelman; W. L. Butler; L. A. Dionne; et al. (American Journal of Potato Research, 1958)

Sectional notes - H. W. Poulsen; H. G. Zuckerman; C. H. Metzger; W. B. Ward; W. C. Edmundson; E. R. Bennet; R. A. Jehle; A. B. Beaumont; John S. Gardner; E. L. Newdick; Frank W. Hussey; E. J. Wheeler; et al. (American Journal of Potato Research, 1934)